ASSOCIATION OF MATERNAL FACTORS TOWARDS ACUTE DIARRHOEAL EPISODES IN UNDER FIVE CHILDREN IN CHHINDWARA DISTRICT: A CROSS-SECTIONAL STUDY - NANDURKAR, PAWAN; UPADHYAY, RITESH; ARYA, SHASHIKANT; DANDOTIYA, DILEEP (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Diarrhea is widely documented as a major cause of childhood morbidity and mortality in countless developing countries, particularly in India. According to the World Health Organization (WHO) report, diarrheal diseases are still leading causes of mortality and morbidity in children below 5 years of age. Objective: The present study done to estimate the association amid maternal factors and prevalence of acute diarrheal illnesses in children below 5 years of age in Chhindwara district. Methods: This community-based and cross-sectional study conducted in the urban field practice area attached to Department of Community Medicine of Chhindwara Institute of Medical Sciences, Chhindwara, from January 2019 to December 2019 was aimed to estimate the connotation between maternal factors and prevalence of acute diarrheal diseases in children under 5 years of age in Indian locations. Study tools included a pre-structured questionnaire. Baseline information of education area was taken from the Urban Primary Health Centre in the catchment area of medical college, Chhindwara. Data were arrived in Microsoft Excel spreadsheet to perform analysis. Results: In our study, 310 mothers who used to take bath daily of which 58 (19.9%) had diarrheal episodes, whereas out of 18 mothers who do not take bath daily, 11 (61.1%) had diarrheal episodes. Further, 292 mothers of children who castoff to wash their hands daily earlier the meals of which 58 (15.8%) children had diarrheal events, whereas out of 7 (38.9%) mothers who did not wash their hands before meals, 27 (12%) children had diarrheal incidents. Conclusion: The present study indicated that maternal factors bear an important impact on morbidity caused by diarrhea.